2019
DOI: 10.1002/jpen.1589
|View full text |Cite
|
Sign up to set email alerts
|

Resting Energy Expenditure Measured by Indirect Calorimetry in Obese Patients: Variation Within Different BMI Ranges

Abstract: Background: The adequate provision of energy for obese patients by estimation without indirect calorimetry (IC) is challenging. The goal was to establish values of kilocalories per kilogram (kcal/kg) for patients in different ranges of body mass index (BMI [kg/m 2 ]) comparable to resting energy expenditure (REE [kcal/kg/d]) measurements by IC. Methods: In 63 overweight (OW) hospitalized patients with BMIs (25.0-29.9) or obesity (OB; ࣙ30), the REE was measured in fasting and fed states. IC was performed with D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
2
0
0
Order By: Relevance
“…We have also observed that increasing BMI and female gender were independent determinants of an increase in EE adjusted for IBW after adjustment for several clinical factors. Our data regarding an increasing IBW-adjusted EE with increasing BMI are similar to the findings of others [ 25 , 26 ]. Gender difference in EE has been reported in critically ill patients by Drolz et al [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…We have also observed that increasing BMI and female gender were independent determinants of an increase in EE adjusted for IBW after adjustment for several clinical factors. Our data regarding an increasing IBW-adjusted EE with increasing BMI are similar to the findings of others [ 25 , 26 ]. Gender difference in EE has been reported in critically ill patients by Drolz et al [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…Regarding BMI, we recognize that the sample was composed by obese individuals including participants with a wide range of BMI, covering the 3 groups defined by the WHO to classify the degree of obesity. However, in our study, BMI did not influence either bias or weight-adjusted RMR, a finding corroborated by a study conducted in Brazil with a sample composed of obese but hospitalized individuals, which aimed to define the best RMR value in kcal/kg, considering the class and/or the BMI range of the patients and observed that there was no difference in RMR values between the different BMI classes in the fasting state ( 35 ).…”
Section: Resultssupporting
confidence: 87%
“…Both techniques -direct and indirect calorimetry -have been developed simultaneously, cross-validating mutually [7,8]. Nowadays, indirect calorimetry is the main technique used to express the energy cost of physical activities [9,10]. This energy is expressed in multiples of the resting metabolic rate (RMR), being the metabolic equivalent (MET) the unit used (1 MET corresponds to the consumption of 3.5 ml kg − 1 min − 1 of O 2 ).…”
Section: Introductionmentioning
confidence: 99%